2004
DOI: 10.1016/j.mce.2004.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-selective determinants in catfish gonadotropin seat-belt loops

Abstract: Mammalian gonadotropins are highly selective. Charge differences between the Cys 10-11 sequence of FSH␤ and LH␤/CG␤ seat-belt loops determine the ability of these hormones to interact with the LH-R. Selective FSH-R binding is mainly dependent on the presence of an FSH␤-specific sequence between Cys 11-12 of the seat-belt loop. Intriguingly, African catfish LH␤ (cfLH␤) lacks a positively charged Cys 10-11 region and stimulates both catfish LH-R and FSH-R with comparable potencies. Our studies on the promiscuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…These results confirm previous data obtained using Xenopus laevis oocytes expressing Senegalese sole Fshra and Lhcgrba and European sea bass recombinant gonadotropins [6]. The promiscuous activation of the Fshra by Lh has also been reported in some salmonids [7], catfish [8][9][10], and cyprinids [11,12], but in other teleosts, such as the rainbow trout [15], Manchurian trout [16], and European sea bass [17,18], each gonadotropin seems to exclusively activate specific cognate receptors. Our observations suggest that the cross-activation of the Fshra by Lh is a conserved mechanism in acanthomorph teleosts such as the Senegalese sole.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results confirm previous data obtained using Xenopus laevis oocytes expressing Senegalese sole Fshra and Lhcgrba and European sea bass recombinant gonadotropins [6]. The promiscuous activation of the Fshra by Lh has also been reported in some salmonids [7], catfish [8][9][10], and cyprinids [11,12], but in other teleosts, such as the rainbow trout [15], Manchurian trout [16], and European sea bass [17,18], each gonadotropin seems to exclusively activate specific cognate receptors. Our observations suggest that the cross-activation of the Fshra by Lh is a conserved mechanism in acanthomorph teleosts such as the Senegalese sole.…”
Section: Discussionsupporting
confidence: 90%
“…By using highly purified gonadotropin preparations or homologous recombinant hormones, it has also been shown that the role of gonadotropins in teleost spermatogenesis seems to be more complex than in mammals. Ligandbinding studies indicate that teleost Fshra shows a preference for Fsh, but it can also be activated by Lh [7][8][9][10][11][12][13][14]. However, such receptor promiscuity is apparently not found in the rainbow trout (Onchorynchus mykiss) [15], the Manchurian trout (Brachymystax lenok) [16], or the European sea bass (Dicentrarchus labrax) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The promiscuous response of the sbsLhr to mammalian FSHs (hFSH and bFSH) but not to sea bass Fsh could have its basis in the higher similarity in sequence and structure of mammalian FSHs to sea bass Lh than to sea bass Fsh, as we previously proposed [20]. On the other hand, the very weak response of sbsFshr to hFSH, together with the fact that many residues described as important for hFSH/hFSHR binding [53] are lacking in sea bass [20], or that specificity determinants in fish b subunits are not related to charge differences as in mammals [54], would recommend caution when using mammalian models to explain fish Fsh-receptor interactions.…”
Section: Discussionmentioning
confidence: 84%
“…The selectivity of gonadotropin ligand/receptor interaction in mammals is well defined: FSH and LH bind to their respective cognate receptors specifically and show little cross-reactivity (0.01%-0.1%) (61,62). In contrast, the bioactivity of fish gonadotropins seems to be less well separated as a result of promiscuous ligand-receptor interactions (26,27,(63)(64)(65)(66). Most of the evidence has suggested that the wider but still limited functional selectivity of FSHR for both FSH and LH may depend on the fish species or taxa, whereas fish LHR, like its mammalian counterpart, seems to be more specific for its ligand (1).…”
Section: Discussionmentioning
confidence: 99%